Religious Risks as a Threat to State Security in Interconfessional Regions - Silayeva, Zoya V. (Journal of History Culture and Art Research, 2017)
This paper is devoted to the study of religious risks, which create a direct or indirect possibility of inflicting damage to both an individual and a multi-confessional state. Particular attention is paid to the crisis of religious identity and the growth of proselytism. The paper involves analysis of the consequences of globalization, religious conflicts and religious migration. Various technologies used by external forces to form new values amid complex socio-political processes were also considered. To study the stated topic, a synthetic approach was used to identify the most significant directions of socio-political changes through studying the shifts in the system of value and behavioral patterns of both believers and neophytes that can cause an increase in religious tension. In the course of the research, the author came to the conclusion that religious risks develop under the influence of certain conditions and factors often created and used purposefully to demonstrate the religious diversity of the internally contradictory integrity of a multi-confessional state, deepen social inequality and exacerbate socio-political tensions caused by a political-ideological confrontation and identity differences. The success of external forces in the situation destabilization is largely due to an incorrect assessment of threats. In order to prevent this, it is necessary to rethink the role of religion in the context of globalization and rapid socio-political transformation, as well as the religious factor in explanatory models of social development.